Sesquiterpenes α-humulene and β-caryophyllene oxide enhance the efficacy of 5-fluorouracil and oxaliplatin in colon cancer cells - Ambrož Martin; Šmatová Markéta; Šadibolová Michaela; Pospíšilová Eva; Hadravská Pavlína; Kašparová Michaela; Skarková Veronika Hanušová; Králová Věra; Skálová Lenka (Acta Pharmaceutica)
The present study is designed to find out if sesquiterpenes, α-humulene (HUM), valencene (VAL), β-caryphyllene-oxide (CAO) and trans-nerolidol (NER), are able to improve the antiproliferative effect of classical cytostatic drugs, 5-fluorouracil (FU) and oxaliplatin (1,2-diaminocyclohexaneoxalato-platinum, OxPt), in colon cancer cell lines Caco-2 and SW-620. In addition, the possible mechanisms of sesquiterpene action are studied. The results show significant ability of HUM and especially of CAO to enhance the anti-proliferative effects of FU and OxPt in cancer cell lines Caco-2 and SW-620. On the other hand, VAL and NER are ineffective. The action of CAO could be partly based on its ability to disrupt the mitochondrial membrane potential and to activate initiator caspases, but other mechanisms are probably also involved. Based on these results, CAO seems to have the potential for combination therapy of colon cancers and deserves further study.